PENERAPAAN LAYANAN PENCETAKAN ULANG KTP PADA APLIKASI KEPENDUDUKAN SECARA ELEKTRONIK (LAKSE) DI KOTA BATAM - dimaz fathurokhman, dimaz fathurokhman; Karol Teovani Lodan, Karol Teovani Lodan (LPPM Universitas Putera Batam, 2023)
In conducting public services, there are often problems such as long queues and long waiting times. Many people complained about the offline service due to time constraints and the tight schedules they have. In order to simplify and accelerate the process of making population documents, the Population and Civil Registration Office (Disdukcapil) together with the Communication and Informatics Office (Kominfo) of Batam City created the Electronic Population Service Application (LAKSE). The purpose of this research is to find out the implementation of Electronic Population Service Application (LAKSE) which focuses on ID card reprinting in Batam City. The type of research method used is descriptive qualitative. The result of the research shows that the service of making Identity Card (KTP) in Batam City is still done manually, and for now the LAKSE application only allows society to do reprint service of KTP that is lost or damaged and this application has not been widely spread in society and also experienced technical issues such as lack of understanding in operating it and error problems in the LAKSE application which caused delays in the process of services provided. Keywords: Services, KTP, Application, LAKSE.